Prospects For Comprehensive Treatment Of Recurrent Supulative Otitis Media In Children (Eurasian Medical Research Periodical, 2024)
Purpose of the study is to study the etiology, pathogenesis, features of the clinical course of recurrent purulent otitis media in children and evaluate the effectiveness of complex treatment.